The Role of the Turkey Secularization Movement in the Collapse of The Ottomans Empire - Luqman Al Hakim; Muhammad Faiz (Universitas Darussalam Gontor, 2021)
Secularism is a product of Western thought that negates the role of religion in state institutions. In Turkey, this thought was carried out at the Tanzimat era of the Ottoman Turkish dynasty which aimed to make the Ottoman Turks more advanced and modern by adopting western values. The main proponent of this movement is The Young Turks which is a revolutionary movement that wants to replace the laws and regulations of the Ottoman Turks with laws that applied in the West. This movement has the support of extremist Jews (Zionism), Western media, and the Freemasonry movement. It was through their secularization agenda that the Ottoman dynasty gradually weakened and collapsed and was replaced by the secular republic of Turkish. This research using qualitative methods base on descriptions, the result obtained from the research are to know early the concept and application of secularism in Khilafah Turkish Ottoman. As well as being a lesson for Muslims and its impact on the sustainability of Islam itself. The contribution of this research can enrich scientific knowledge in the historical field, especially regarding the political and social aspects of Islam in the Uthmani Khilafah.